The Function of Immune Cells into Breast Tissue and the Use of Immunotherapy to Treat Breast Cancer. Review Article - Noor Al- Huda Ali A. H. Saeed; Khetam H. Rasool; Ban Talib Elhaboby; Liqaa Jameel Ibraheem (Scholars Digest Publishing, 2023)
Both healthy breast tissue and breast cancer contain immune cells. The composition and location of the immune cell subtypes in such tissues were reviewed to facilitate a better understand of their critical role in breast cancer\prevention and treatment. To determine the kind, location, distribution, and function of immune cells in healthy breast tissue in addition to in situ or invasive breast cancer, we reviewed the literature. Immune cells of normal breast tissue were situated largely inside the epithelial components in breast ductal lobules. innate immunity (NK; CD68+; CD11c+) cells and adaptive immunity (most frequently CD8, but also CD4 and CD20) are represented by immune cell subtypes; The most prevalent subtype and mainly effector memory cells are CD8 cells. Immune cells may detect neoantigens, as well as endogenous and external ligands, and can play a role in immunosurveillance and chronic inflammation. Increased immune cell infiltrates across tumor parenchyma and stroma, including CD4 and CD8 granzyme B cytotoxic T cells; B cells; macrophages; and dendritic cells, are indicative of breast cancer progression. Breast cancer tumor-infiltrating lymphocytes may act as predictors of survival and chemotherapy response. Metastatic breast cancer may be able to regress thanks to experimental adoptive transfer tactics of lymphocytes that have infiltrated breast tumors, and these strategies may also promote the creation of novel T-cell immunotherapy strategies for treating breast cancer. In summary, immune cells of breast tissues play as significant role in the development of breast cancer. Understanding these roles has significant ramifications for breast cancer prevention and treatment.